The roles of hepatokine and osteokine in liver-bone crosstalk: Advance in basic and clinical aspects - Li, Zhanghao; Wen, Xiaoxin; Li, Nanxi; Zhong, Chuanxin; Chen, Li; Zhang, Feng; Zhang, Ge; Lyu, Aiping; Liu, Jin (Frontiers in Endocrinology, 2023)
Both the liver and bone are important secretory organs in the endocrine system. By secreting organ factors (hepatokines), the liver regulates the activity of other organs. Similarly, bone-derived factors, osteokines, are created during bone metabolism and act in an endocrine manner. Generally, the dysregulation of hepatokines is frequently accompanied by changes in bone mass, and osteokines can also disrupt liver metabolism. The crosstalk between the liver and bone, particularly the function and mechanism of hepatokines and osteokines, has increasingly gained notoriety as a topic of interest in recent years. Here, based on preclinical and clinical evidence, we summarize the potential roles of hepatokines and osteokines in liver-bone interaction, discuss the current shortcomings and contradictions, and make recommendations for future research.